Maternal Outcome and Prevalence of Placenta Previa Among Pregnant Patients - Saira Nazneen, Naila Bukhari (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Placenta previa is a serious complication, associated with feto-maternal complications, and mortality worldwide. Its incidence varies in different regions of the world, so for the sake of determining its prevalence in our health setup, this study is conducted. The primary goal of this study is to determine the outcome and prevalence of placenta previa among pregnant patients presented at khyber teaching hospital peshawar MTI. Material and Methods: A total of 6400 patients presenting to our department for elective and emergency caesarean section were examined for placenta previa. 120 patients were diagnosed with placenta previa. Maternal outcome was assessed in patients with placenta previa. Results: The frequency of placenta previa in 6400 patients presenting for emergency caesarean section was 1.87%. Antenatal bleeding was found in 70 (58.3%) patients, anemia was found in 43 (35.8%) and postnatal bleeding was found in 10 (8.3%). Conclusion: Prevalence of placenta previa was 1.84%. Antenatal bleeding, anemia and postnatal bleeding were adverse maternal outcomes. Keywords: Maternal, neonatal, outcome measures, placenta accreta spectrum, PAS, placenta previa